1996
DOI: 10.1002/(sici)1096-9896(199607)179:3<238::aid-path566>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

bcl‐1 REARRANGEMENT AND CYCLIN D1 PROTEIN EXPRESSION IN MANTLE CELL LYMPHOMA

Abstract: Centrocytic lymphoma, or mantle cell lymphoma (MCL), is characterized by a chromosomal translocation t(11;14) (q13;q32) involving the bcl-1 locus on chromosome 11. Cyclin D1 is a cell-cycle regulatory protein essential for G1-S transition and has been identified as a potential transforming gene affected by the translocation. In this study, 32 cases of MCL were analysed for the bcl-1 rearrangement and cyclin D1 protein expression. In 17 cases, a rearrangement at the major translocation cluster of bcl-1 could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 0 publications
0
27
1
1
Order By: Relevance
“…Mantle cell lymphoma is characterised by a translocation between the Cyclin DI gene on chromosome 11 and the immunoglobulin heavy chain gene on chromosome 1422-25 in about 70% of cases.26 This translocation results in the overexpression of Cyclin D 1 in the nuclei of the tumour cells of MCL,27 which is also seen in cases of MCL without detectable molecular evidence of t (1 1;14).26 27 With one exception, expression of Cyclin D1 has not been seen in B-SLL. It has also been recorded rarely in hairy cell leukaemia and plasmacytoma.25 Our studies confirm Cyclin D1 as the most reliable marker for the distinction between B-SLL and MCL.…”
Section: Discussionmentioning
confidence: 99%
“…Mantle cell lymphoma is characterised by a translocation between the Cyclin DI gene on chromosome 11 and the immunoglobulin heavy chain gene on chromosome 1422-25 in about 70% of cases.26 This translocation results in the overexpression of Cyclin D 1 in the nuclei of the tumour cells of MCL,27 which is also seen in cases of MCL without detectable molecular evidence of t (1 1;14).26 27 With one exception, expression of Cyclin D1 has not been seen in B-SLL. It has also been recorded rarely in hairy cell leukaemia and plasmacytoma.25 Our studies confirm Cyclin D1 as the most reliable marker for the distinction between B-SLL and MCL.…”
Section: Discussionmentioning
confidence: 99%
“…2 3 Interest in a possible role of cyclin D1 in tumorigenesis has grown since experiments demonstrated that induction of cyclin D1 in cells arrested in the early G1 phase by transfection with pRB was sufficient for cell cycle completion 4. Further, cyclin D1 overexpression has been reported in several tumours including parathyroid adenomas,5 mantle cell lymphoma,6 7malignant melanoma of the skin,8 as well as carcinomas of the breast, lung, liver, oesophagus, urinary bladder, head and neck, vulva, and uterine cervix 8-14…”
mentioning
confidence: 99%
“…The immunohistochemical detection of overexpression of cyclin D1 is important for the histological diagnosis of mantle cell lymphoma in lymph node biopsy (Yang et al 1994;de Boer et al 1995;Swerdlow et al 1995Swerdlow et al , 1996Zukerberg et al 1995;Ott et al 1996;Majlis et al 1997;Vasef et al 1997;Aquilera et al 1998). Cyclin D1 protein overexpression is the result of the BCL-1 rearrangement, which is detectable in 70-80% of mantle cell lymphomas (Williams et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The International Lymphoma Study Group included mantle cell lymphoma in the REAL classification . A rearrangement of the bcl-1/cyclin D1 oncogene is usually present (Williams et al 1991) and leads to overexpression of cyclin D1 protein (Yang et al 1994;de Boer et al 1995;Swerdlow et al 1995Swerdlow et al , 1996Zukerberg et al 1995;Ott et al 1996;Majlis et al 1997;Vasef et al 1997;Aquilera et al 1998). We investigated the expression of cyclin D1 protein in 108 patients with leukaemic B-lymphoproliferative disorders and describe its importance for the differentiation of the leukaemic phase of these disorders.…”
Section: Introductionmentioning
confidence: 99%